The city beyond the sea eaudiobook - Thomson, Pari (Greenwild, 2024)
"Nomvete gives a passionate performance, establishing a unique voice for each character. Listeners and environmentalists alike will be intrigued by this fantastical world and the characters Nomvete brings to life in this grand adventure" — AudioFile on Greenwild: The World Behind the Door Daisy Thistledown's epic adventure continues in the spellbinding sequel to the New York Times bestseller Greenwild , which A.F. Steadman (bestselling author of Skandar and the Unicorn Thief ) praised as "Phenomenal . . . If you don't believe in magic, you will after you've read Greenwild ." In a land ruled by water, treachery runs deep, and Daisy Thistledown's journey is just beginning... Desperate to join the expedition searching for her mother and the other missing Botanists, Daisy and her friends abandon the safety of magical Mallowmarsh. Facing danger on the high seas, they find themselves pursued across the waves by ruthless Grim Reapers. But they will need help to defeat these dangerous enemies. Their greatest hope: to find the legendary Iffenwild, a mysterious city hidden beyond the sea and lost to time. New discoveries await, and a strange botanical magic stirs beneath the waves. It will take all of Daisy's courage and determination—and the trust of an unexpected new friend—if she is to save the Greenwild from a terrible fate. Don't miss out on this exciting trilogy! Book 1 - Greenwild: The World Behind the Door Book 2 - Greenwild: The City Beyond the Sea Book 3 - Coming soon! A Macmillan Audio production from Farrar, Straus and Giroux.